Analisis Ketersediaan Obat pada Sebelum dan Selama Pandemi COVID-19 di RSUD Bali Mandara Provinsi Bali - Sitepu, Eme Stepani; Ayuningtyas, Dumilah; Junadi, Purnawan; Satibi, Satibi; Daniel, Rizki (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
The availability of drugs needs to be guaranteed to meet the needs of patients both in terms of quantity and type. This can be realized if drug management in the hospital is carried out effectively and efficiently. Factors that influence this include the suitability of planning methods, drug procurement, availability of e-catalog, good human resource competence, and budget adequacy. The challenges in the COVID-19 pandemic situation in 2020 are activity restrictions that affect the distribution of drugs and raw materials while the demand for drugs increases. This study aims to analyze the level of drug availability before the pandemic and during the COVID-19 pandemic at the Bali Mandara Provincial General Hospital. This study was conducted from September to December 2023 using a quantitative approach. Data were collected retrospectively using stocks, and drug procurement from 2019 to 2022. The results showed no incidents of poor drug stocks in 2019-2022. However, there was an increase in the percentage of safe category for the needs of 12-18 months from 2019 to 2022 by 42.5%, 44.4%, 69.1%, and 65.7%, respectively. There are still excessive stocks above 18 months although the percentage is decreasing at 37.9%, 26.2%, 21.6%, and 28.8%, respectively. The decrease in drug items with availability levels of more than 60 months was 15.7%, 8.6%, 7.0%, and 4.1%, respectively. There were expired drugs before and during the COVID-19 pandemic but the value of expired items decreased from Rp. 370,221,269.27 in 2019 to Rp.93,787,747.28 in 2022. Conclusion: The Hospital Pharmacy Department can fulfill the need for drugs before and during the COVID-19 pandemic, indicated by no incidents of drug shortages. However, it is necessary to manage drugs more efficiently, because there are still drugs without use in a year and expired drugs, although the percentage has decreased during the COVID-19 pandemic.